Doing well or doing good? Extrinsic and intrinsic CSR in Switzerland - Looser, S.; Wehrmeyer, Walter (HIS Hochschul-Informations-System GmbH, 2015)
Arguably, within Corporate Social Responsibility (CSR) the intrinsic motive is more significant than the extrinsic because the former induces a stronger involvement. Others showed that a behaviour attributed to extrinsic motives is mostly perceived as dishonest and misleading. This highlights how important the underlying motivation is for the perception, and thus, design and effectiveness of CSR frameworks. This study discusses these divergent motives with two focus groups: together with seven owner-managers of Small and Medium-sized Enterprises (SME) and seven managers of large companies. The results show that CSR implementation in Swiss SMEs is related more strongly to moral commitment than to profit-maximisation. Accordingly, small business CSR emerges from the nexus of mission and value-set and the sociological tradition of the stewardship concept. This contrasts the extrinsically motivated approach of the large companies under research. In sum, this study showed that CSR is meaningful and justifiable even if it is not profitable in the first place.